Sea urchins like Zinc oxide nanometric mitigating Meloidogyne incognita infection in eggplant - Amir Khan; Manar Fawzi Bani Mfarrej; Mohd. Farhan Khan; Shahbaz Khan; Peiter Malan; Saurabh C. Saxena; Mohd. Muddassir; Faheem Ahmad (Cogent Food & Agriculture)
This study focused on the nematicidal potential of sea urchin-like zinc oxide nanometrics (SUZN) against the root-knot nematode Meloidogyne incognita. XRD, SEM, UV-vis spectroscopy, TEM, and EDX have been utilized to characterize the SUZN. Various SUZN concentrations (150–750 ppm) were examined for their implications for M. incognita second-stage juveniles (J2s) and egg masses, including mortality as well as hatching inhibition. The largest J2s hatching inhibition (83.07%) was seen at 750 ppm SUZN after 48 hours of incubation, whereas the lowest hatching occurred at 150 ppm when compared to the control. SUZN illustrated increased nematicidal efficiency with increasing concentration and incubation duration. LC50 values for J2s were calculated at various time points. In root-dip trials, all SUZN doses substantially reduced J2s penetration into eggplant roots relative to the untreated control. The study emphasizes SUZN’s strong nematicidal activity against M. incognita, suggesting its promise as a long-term alternative to chemical nematicides for root-knot nematode management while reducing the environmental concerns associated with traditional pesticides.